Nilai-Nilai Tasawuf dalam Konsep Pendidikan Islam Menurut Hamka Roza Susanti - Susanti, Roza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study is to understand the values ​​of Sufism in Islamic education according to Hamka. This research is a qualitative research using a library research approach using books and other literatures as the main object of research, for further content analysis that will be used in drawing conclusions. The results of the research, Hamka is an Islamic thinker who is famous for his concept of